Mapping the landscape of green banking strategies: a bibliometric approach - Taneja, Sanjay; Bansal, Neha; Johri, Amar; Asif, Mohammad; Shamsuddin, Zelhuda (Frontiers in Sustainable Cities, 2024)
Green banking (GB) strategies are a set of financial practices and activities implemented by banks to encourage sustainability, environmental responsibility, and low-carbon impact. This bibliometric study examines the present state of research in this field by utilising the Scopus database for data retrieval and VosViewer for network analysis. A total of 149 researches were retrieved from the Scopus and analysed using the VosViewer software following the PRISMA guidelines.The study examines year-by-year publication patterns, top-cited articles, contributing countries, journals, co-citation analysis of authors, and co-occurrence analysis of keywords. Strategies such as online banking, solar ATMs, construction of green buildings, and making provisions for green loans are identified as the key GB strategies that can be adopted by the banks. Furthermore, the fundamental challenges banking organisations encounter while implementing GB strategies are underlined. The study suggests that "green brand image," "green audit," "environmental economics,"and "carbon footprint" can be considered as a area of interest in future. The study provides researchers, policymakers, regulators, and financial institutions with valuable insights by presenting the current state of green banking research and identifying emerging areas for further exploration.